An Evaluation of the Effectiveness of the Community Support Grant (CSG) In Early Childhood Development & Education (ECDE) Centers in Embu West District, Kenya - Kamau, Bonface; Kamau, Joyce; Kamau, Margaret; Koech, Peter Kibet (My University, 2015)
This paper discusses findings of an evaluation of the effectiveness of the Community Support Grant (CSG) in Embu West District. The evaluation was done to evaluate the impact of Early Childhood Development & Education (ECDE) services on child outcome. The main objectives of (CSG) were; To increase access to ECDE, to improve child health and nutrition status, and to improve qualified personnel and reduce drop outs and repetition at lower primary schools. This was to be done by having CSG funding support translated into; Teaching and learning materials, new classrooms, new furniture, repaired classrooms, repaired furniture, new toilets, basic construction tools and materials for volunteer community labor and augmentation of one or two full time ECDE teacher(s) salary. The findings showed that; the qualities of ECDE services have improved as majority of teachers are motivated by the top up of their salaries, due to the procurement of furniture by most of the ECDE centers the children were now comfortable hence more alert and active learning. The chairs were also child-size, hence supporting child development unlike desks used, instructional materials were also previously improved quality of teaching and learning as well as the classroom environment, and construction of toilets and buying of water tanks is bound to have positive impact on the health of the children. However, there were challenges that were seen to strain the expected positive consistence in the efforts of providing quality education to the children. Therefore prequalification was not done, there was Poor record keeping in most of the schools, most of the head teachers though trained on CSG were not keen on record keeping and there was Lack of community support on the program. To conclude it was very true to say that Community Support Grant had met a desirable effect in the education of Embu West District Early Childhood Education and Development children. Thus, the paper calls for concerted efforts by the stakeholders to addressee the challenges experienced in Kenyan early childhood centers. “It takes the whole village to educate a child”.
Keywords: Embu West District; Community Support Grants; Early Childhood Development; Education